Structural Development of Russian Economy: Assessing the Condition and Prospects of Speeding-Up - O. V. Morozov; M. A. Vasiliev (Вестник Российского экономического университета имени Г. В. Плеханова)
In the practice of state governance economic development is usually estimated by comparing macro-economic indicators for the period being evaluated with relevant preceding periods. The article studies a non-conventional – structural approach to estimating the development of sectoral structure of Russian economy. The period of 10 years, i. e. from 2011 to 2020 was analyzed, at the same time the possibility of accelerated development in the medium-term (2023) and long-term (2036) periods was investigated. The authors provide theoretical foundations of the research, indicators of structural development, the procedure and algorithms of their estimation. The criterion and quality model of passing-over from the actual condition to the optimal combination of sector scales were identified. By comparing the actual and model (estimated) indicators of sector scales the trend and nature of structural development of national economy were evaluated, as well as its capacity to develop rapidly in future periods. The findings show that harmonization of indicators of diversity and uniformity, changeability and stability in sectoral structure forms a structural precondition for the development of national economy. These indicators can be used by bodies of state governance in the process of devising strategy of accelerated development of economy in general and its industries.